Higher education manager's handbook : effective leadership and management in universities and colleges - McCaffery, Peter 1952- (Routledge, 2010)
This bestselling guide builds upon its original strengths and remains an engaging, accessible and highly enjoyable read. Written from the unique perspective of the Higher Education manager, it offers practical advice that can be implemented immediately by managers and university leaders at all levels.